An organizational perspective on fading system-ness: Insights from Ennahda’s post-specialization period (2016–2021) - Fulco, Carmen (Politics and religion, 2025)
About a decade after the Arab Uprisings, the Tunisian Ennahda party experienced the exodus of several high-profile leaders. Motivated by the party’s growing factionalism and shrinking support, this article investigates the organizational factors that account for the low system-ness of an Islamist-born party following major organizational changes. It does so by drawing on interview data and organizational developments that unfolded inside Ennahda (2016-2021). In a framework that intersects the field of party politics and organization studies, this article argues that the major factors that account for Ennahda’s low system-ness include (i) an inefficient and inadequate theorization of the need for the party’s specialization in political activities, (ii) a problematic identification with the subsequently refashioned organizational identity, and (iii) an uneasy coexistence of distinct group identities involved in separate processes of organizational identity recrafting. This article concludes by challenging the way scholars traditionally conceive coherence, cohesion, and "change" in religious parties.